2021
DOI: 10.3390/polym13234258
|View full text |Cite
|
Sign up to set email alerts
|

Polydimethylsiloxane Composites Characterization and Its Applications: A Review

Abstract: Polydimethylsiloxane (PDMS) is one of the most promising elastomers due its remarkable proprieties such as good thermal stability, biocompatibility, corrosion resistance, flexibility, low cost, ease of use, chemically inertia, hyperplastic characteristics, and gas permeability. Thus, it can be used in areas such as microfluidic systems, biomedical devices, electronic components, membranes for filtering and pervaporation, sensors, and coatings. Although pure PDMS has low mechanical properties, such as low modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(93 citation statements)
references
References 131 publications
4
87
2
Order By: Relevance
“…The arithmetic average of the tensile strength of samples manufactured by the conventional method is approximately 2.36 MPa, which is consistent with the studies reported in the literature [15]. For the MVC samples, the tensile strength corresponds to 3.27 MPa.…”
Section: Tensile Testsupporting
confidence: 90%
See 2 more Smart Citations
“…The arithmetic average of the tensile strength of samples manufactured by the conventional method is approximately 2.36 MPa, which is consistent with the studies reported in the literature [15]. For the MVC samples, the tensile strength corresponds to 3.27 MPa.…”
Section: Tensile Testsupporting
confidence: 90%
“…The maximum tensile strength of the samples manufactured with the MVC improved about 39% when compared to the samples manufactured by the conventional method. When it comes to the maximum strain of the samples, the results were 0.48 and 0.81 for the samples manufactured by the conventional method and manufactured in the MVC, respectively, being consistent with the literature [15]. Hence, these results show that was an improvement bigger than 65% when compared to samples manufactured using MVC and manufactured using the conventional method.…”
Section: Tensile Testsupporting
confidence: 88%
See 1 more Smart Citation
“…Adding waxes such as paraffin or beeswax to PDMS has been demonstrated to potentially increase the corrosion resistance, hydrophobicity and thermal and optical properties of PDMS, which is useful in applications such as sensors, wearable devices and superhydrophobic coating [ 83 ].…”
Section: Pdms Propertiesmentioning
confidence: 99%
“…An important characteristic of blood vessels is the existence of soft tissues, which have a behavior called hyperelasticity [10]. Hyperelastic materials have a mechanical behavior characterized by a high deformation before reaching the breaking strength [11,12]. Due to the risks involved, it is very difficult to analyze in vivo the biomechanical behavior of blood vessels, particularly in the region of the aneurysm [13].…”
Section: Introductionmentioning
confidence: 99%